Association of septal late gadolinium enhancement on cardiac magnetic resonance with ventricular tachycardia ablation targets in nonischemic cardiomyopathy. (27th October 2020) - Kuo, Ling; Liang, Jackson J.; Han, Yuchi; Frankel, David S.; Santangeli, Pasquale; Callans, David J.; Zado, Erica S.; Marchlinski, Francis E.; Desjardins, Benoit; Nazarian, Saman
Abstract: Background: Ablation of septal substrate‐associated ventricular tachycardia (VT) in patients with nonischemic cardiomyopathy (NICM) is challenging. We sought to standardize the characterization of septal substrates on late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) and to examine the association of that substrate with VT exit and isthmus sites on invasive mapping. Methods: LGE‐CMR was performed before electroanatomic mapping and ablation for VT in 20 NICM patients. LGE extent and distribution were quantified using myocardial signal‐intensity Z scores (SI‐Z). The SI‐Z thresholds correlating to previously validated voltage thresholds, for abnormal tissue and dense scar were defined. Results: Bipolar and unipolar (electrogram) voltage amplitude measurements from the LV and RV were negatively associated with SI‐Z from LGE‐CMR imaging ( p < .05). SI‐Z thresholds for appropriate CMR identification of septal substrates were determined to be greater than −.15 for border zone and greater than .03 for a dense scar. Among all patients, 34 critical VT sites were identified with SI‐Z distribution in the range of −.97 to .06. Thirty (88.2%) critical sites were located in the dense LGE, 1 (2.9%) in the border zone, and 3 (8.9%) in healthy tissue but within 7 mm of LGE. Of note, critical VT sites were all located at the basal septum close to valves (distance to aortic valve: 17.5 ± 31.2 mm, mitral valve: 21.2 ± 8.7 mm) in nonsarcoidosis cases. Conclusions: Critical sites of septal VT in NICM patients are predominantly in the CMR defined dense scar when using standardized signal‐intensity thresholds.